2023
DOI: 10.21037/tcr-22-2463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the metastatic mechanism and progress in the treatment of breast cancer liver metastasis: a narrative review

Abstract: Background and Objective Breast cancer is the most common malignancy in women, and metastasis to other target organs is one of the main causes of death. Breast cancer liver metastasis (BCLM) has long been a research focus. Enhancing therapeutic effects, optimizing treatment plans and improving the prognosis of patients are major clinical challenges at present. Methods We performed a comprehensive, nonsystematic review of the latest literature to define the current metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…In a meta-analysis conducted in 2014, it was observed that there may be a negative correlation between folate consumption and the risk of bladder cancer. However, this correlation was only observed in retrospective studies and not in prospective studies [78]. A prominent case-control study carried out in the United States, included in the previously mentioned meta-analysis, yielded no substantial correlation between folate consumption and the likelihood of developing bladder cancer.…”
Section: Effects Of Nutrients On Bladder Cancer Progressionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a meta-analysis conducted in 2014, it was observed that there may be a negative correlation between folate consumption and the risk of bladder cancer. However, this correlation was only observed in retrospective studies and not in prospective studies [78]. A prominent case-control study carried out in the United States, included in the previously mentioned meta-analysis, yielded no substantial correlation between folate consumption and the likelihood of developing bladder cancer.…”
Section: Effects Of Nutrients On Bladder Cancer Progressionmentioning
confidence: 93%
“…A study has found that the intake of milk, which is rich in vitamin B2 and B12, is associated with a reduced risk of bladder cancer [80]. However, Brinkman et al and Dugué et al found no correlation between vitamin B6 and B12 and bladder cancer [78,81].…”
Section: Effects Of Nutrients On Bladder Cancer Progressionmentioning
confidence: 99%